An Analysis of Mathematical Literacy Skills in Word Problem Solving among High-Achieving Students - Insania Durrotun Nafisa; Nila Kurniasih; Erni Puji Astuti (Jurnal Inovasi Pendidikan Matematika (JIPM), 2026)
Students’ mathematical literacy in Indonesia remains low based on the results of the international PISA study. This research aims to provide an in-depth description of students’ mathematical literacy skills based on PISA levels and viewed from their mathematics achievement. The study employed a qualitative method with a phenomenological approach. The subjects were selected using purposive sampling, consisting of two eighth-grade students with high achievement. Data collection techniques of included literacy skill tests. Interview, field notes, and documentation. The research instruments used were mathematical literacy test sheets and interview guidelines. Data analysis was carried out through the stages og data collection, data reduction, data display, and conclusion drawing/verification. The results indicate that high-achieving students reached mathematical literacy levels 5 to 6. These students were able to identify information, formulate strategies, perform calculations, and draw as well as communicate conclusions accurately. This study provides practical implications for teachers as a reference in the learning process, particularly in designing PISA-based mathematical word problems to enhance students’ mathematical literacy skills.